(untitled) (Archives of The Medicine and Case Reports, 2021)
Miss AN, female, 17 years old, Muslim, Betawi ethnicity, graduated from elementary school, currently no longer in school. The first febrile seizure patient was four years old. Five to seven years old, patients with recurrent seizures without fever, diagnosed with epilepsy and do not see a doctor regularly. At 14 years, the patient was raped, and since then, the patient has had free sex with many different men. At the age of,16, the patient had seizures up to five times an ay, and one seizure was approximately five minutes. The patient went to a neurologist and was regularly treated with valproic acid and carbamazepine. At the age of 17 years, the patient often got angry when teased and threatened with knives or scissors, had free sex with many men and went to a psychiatrist. The patient has been treated five times in different mental hospitals because he often runs away from home. Currently, the patient is being treated in the psychiatric ward and is receiving 2 x 500 mg of valproic acid, 3 x 200 mg of carbamazepine, 2 x 0.5 mg of Clonazepam and 1 x 50 mg of sertraline. At the time of treatment, the patient is known to be HIV positive and does not need ARV therapy. Patients also planned behavioural therapy and involved patients with activities at Yayasan Pelita Ilmu. It is hoped that this therapy can help overcome the patient’s behavioural and emotional problems.